2019
DOI: 10.1007/s11676-019-01021-9
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship, attained diameter, height and volume of three Paulownia species after 9 years in the southern Appalachians, USA

Abstract: Little is known of the tree and stand dynamics of varied species of planted Paulownia left unmanaged until harvest in the southeastern United States. We sought to remedy this lack of information needed by land managers to make informed decisions by investigating differences in survivorship, attained diameter breast height (DBH), diameter at ground level, total height, tree volume and stand-level volume yields of planted P. elongata, P. fortunei, and P. tomentosa in the cool-moist environment of the southern Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…On the other hand, Paulownia plantations established in the USA on an abandoned agricultural field in Virginia (Johnson et al 2003) 3). Observations of Berg et al (2020) suggested that strong winds might also be another factor affecting the development of Paulownia plantation. Barton et al (2007) observed that the breakage of young stems and branches of Paulownia trees occurred when the wind speed exceeded 40 km•h -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Paulownia plantations established in the USA on an abandoned agricultural field in Virginia (Johnson et al 2003) 3). Observations of Berg et al (2020) suggested that strong winds might also be another factor affecting the development of Paulownia plantation. Barton et al (2007) observed that the breakage of young stems and branches of Paulownia trees occurred when the wind speed exceeded 40 km•h -1 .…”
Section: Resultsmentioning
confidence: 99%
“…or in the Southern Appalachians in North Carolina(Bergman 2003;Berg et al 2020) as well as in Ireland(Olave et al 2015) showed much worse results (Table1) Johnson et al (2003). andBerg et al (2020) described serious problems Growth of Paulownia sp. plantations under various conditions…”
mentioning
confidence: 99%
“…Paulownia is a member of the Paulownia genus (Scrophulariaceae family), native to China and Southeast Asia [8][9][10]. The genus Paulownia (Paulowniaceae family) consists of nine species such as Paulownia fortunei (P. fortunei), Paulownia elongata (P. elongata), Paulownia catalpifolia (P. catalpifolia), Paulownia albiphloea (P. albiphloea), Paulownia tomentosa (P. tomentosa), Paulownia australis (P. australis), Paulownia kawakamii (P. kawakamii), Paulownia fargesii (P. fargesii), and Paulownia taiwaniana (P. taiwaniana) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, paulownia species are not on such lists in Poland. In general, P. tomentosa is considered the most invasive species among others due to its higher resistance to low temperatures [12]. Moreover, hybrid species have theoretically reduced fertility, so they produce less fruit and seeds, which limits their spread.…”
Section: Introductionmentioning
confidence: 99%
“…1-2) P. tomentosa × P. fortunei (no. 3-7), P. tomentosa (no [8][9][10][11][12][13][14][15][16][17][18]…”
unclassified